Compartmentalization of prokaryotic DNA replication - Bravo, Alicia; Serrano-Heras, Gemma; Salas, Margarita (FEMS microbiology reviews, 2005)
It becomes now apparent that prokaryotic DNA replication takes place at specific intracellular locations. Early studies indicated that chromosomal DNA replication, as well as plasmid and viral DNA replication, occurs in close association with the bacterial membrane. Moreover, over the last several years, it has been shown that some replication proteins and specific DNA sequences are localized to particular subcellular regions in bacteria, supporting the existence of replication compartments. Although the mechanisms underlying compartmentalization of prokaryotic DNA replication are largely unknown, the docking of replication factors to large organizing structures may be important for the assembly of active replication complexes. In this article, we review the current state of this subject in two bacterial species, Escherichia coli and Bacillus subtilis, focusing our attention in both chromosomal and extrachromosomal DNA replication. A comparison with eukaryotic systems is also presented.